2022
DOI: 10.1371/journal.pone.0271757
|View full text |Cite
|
Sign up to set email alerts
|

Child emotional and behavioral difficulties and parent stress during COVID-19 lockdown in Sri Lankan families

Abstract: Introduction Understanding parents’ and children’s mental health issues would help design population-specific intervention programs. The present study explored parents’ perceived stress and child emotions and behavior during the COVID-19 lockdown among Sri Lankan families. Methods A cross-sectional survey was conducted among Sri Lankan parents of children aged 11 to 17 years. Validated instruments (Perceived Stress Scale-PSS and Strengths and Difficulties Questionnaire-SDQ) evaluated parental stress, child e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…9,10,12 A small proportion (8.9%) of parents were single (divorced/widowed). Similar results were observed in a previous study by Ashan Athapattu et al 13 and Marchetti et al 14 , were 5.1% and 12.3% of parents were single, respectively.…”
Section: Sociodemographic Detailssupporting
confidence: 91%
“…9,10,12 A small proportion (8.9%) of parents were single (divorced/widowed). Similar results were observed in a previous study by Ashan Athapattu et al 13 and Marchetti et al 14 , were 5.1% and 12.3% of parents were single, respectively.…”
Section: Sociodemographic Detailssupporting
confidence: 91%
“…Research quickly responded to the public health crisis by describing the impact of the pandemic on family functioning and child wellbeing across the world [2,[8][9][10][11][12][13]. What has yet to be understood is how COVID-19 disruptions get inside the family [5,14].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated that, in addition to disruptions in education during the COVID-19 quarantine, there are also changes in the mood, emotions and behavior of children and adolescents (Athapathu, et al, 2022;Braksiek et al, 2022;Christner, 2021;Di Giorgio, 2021;McKune et al, 2021;Pudpong et al, 2023;Rabe et al, 2021;Rathgeb et al, 2022;Spinelli et al, 2021;Wu et al, 2023). Cohen Arazi et al, (2022) conducted a study in which they received opinions from families about children's emotional changes during the pandemic period.…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated that children express their fears in the form of tantrums, crying for no reason, irritability, and shouting. It is mentioned that the interaction of parents with their children is effective in solving psychological and behavioral problems that may occur (Alisinaoğlu, et al, 2020;Athapathu, et al, 2022;Spinelli, 2021). Children's stress responses are affected by parents' emotional regulation and level of exposure to stress.…”
Section: Introductionmentioning
confidence: 99%